1st International Symposium on Gait and Balance in MS: Gait and Balance Measures in the Evaluation of People with MS. (17th June 2012) - Cameron, Michelle; Wagner, Joanne; Zackowski, Kathleen; Spain, Rebecca
Abstract : Gait and balance measures have particular potential as outcome measures in Multiple Sclerosis (MS) because, of the many hallmarks of MS disability, gait and balance dysfunction are present throughout the course of the disease, impact many aspects of a person's life, and progress over time. To highlight the importance and relevance of gait and balance measures in MS, explore novel measurements of gait and balance in MS, and discuss how gait, balance, and fall measures can best be used and developed in clinical and research settings, the 1st International Symposium on Gait and Balance in Multiple Sclerosis was held in Portland, Oregon, USA on October 1, 2011. This meeting brought together nearly 100 neurologists, physiatrists, physical therapists, occupational therapists, nurses, engineers, and others to discuss the current status and recent advances in the measurement of gait and balance in MS. Presentations focused on clinician-administered, self-administered, and instrumented measures of gait, balance, and falls in MS.